Macro Role Plays on Early Childhood Expressive Language Skills - Nurul Khaimah; Arismunandar; Rusmayadi; Herlina; Wahira (Jurnal Pendidikan Anak Usia Dini, 2026)
This study aims to find out the description of the implementation of macro role-playing, find out children's expressive language skills before and after doing macro role-playing activities, and examine the effect of macro role-playing on early childhood expressive language skills. This research method uses a quantitative approach with a simple experimental method. The design used is a pre-experimental design with a one group pretest-posttest design. The data collection technique through observation and documentation of descriptive analysis as a form of data analysis from this study. The results showed that the implementation of macro role-playing was effective and smooth over 8 sessions, with high participation (95%) and simple props support that encouraged imaginative interaction resembling real life, making it suitable for language development., children's expressive language skills improved significantly before (average 0.45 or 41.9%) and after (0.88 or 81.8%) treatment, especially on the indicators of storytelling and spontaneous expression (up to 121%).,  and a significant positive influence was found on macro role play on expressive language skills (Wilcoxon test: T=35 < 151 tables; Z=-5.62, p<0.001), proving that this method is effective as a game intervention for early childhood oral language development.